Estrategias para la enseñanza de la producción de textos argumentativos en el área de ciencias biológicas - Zambrano-Valencia, Juan David; Orozco-Cardona, Andrés Felipe; Caro-Lopera, Miguel Angel (Colombian Applied Linguistics Journal, 2016)
This research paper focuses on the following question: based on the reading of disciplinary texts, what pragma-linguistic procedures could support the construction of a didactic proposal about the line of thinking production in biological sciences? We opted for action-research method from the perspective of Elliott (1993, 2000), and we rely primarily on the theoretical assumptions of Stephen Toulmin (1977, 2003, 2007) and Anthony Weston (2005), on what is referred to argumentation, as in the postulates of the maternal language teaching (Camps, 1995, 2004; Alvarez, 2005 and 2010, Camargo and Uribe, 2007), the textual linguistics (Bernardez, 1982 and 1994; De Beaugrande and Dressler, 1997) and the Adam´s argumentative prototypical sequence (1985, 1992, 1995). Validated by discussion groups of teachers of the field for two semesters, five strategic fronts appeared as a direct result of the project: 1. The configuration of the dispositio: argue from the structure; 2. Recognition of the source: argue from authority; 3. The resource of the definition: argue from the versatility; 4. The use of analogy: argue from proximity; 5. The value of the discussion: argue from distance.